PENGARUH LINGKUNGAN KERJA, ROLE STRESS, DAN KOMPENSASI FINANSIAL PADA KEPUASAN KERJA DI HOTEL DEKUTA BALI - Utama, Ida Bagus Budi; Surya, Ida Bagus Ketut (E-Jurnal Manajemen, 2019)
The purpose of this study is to explain the influence of the work environment, role stress, and financial compensation on employee job satisfaction. The population of this research is all employees of Dekuta Hotel. The sampling technique in this study used saturated samples, so that the number of samples obtained was 52 employees. Methods of collecting data using questionnaires. The analysis technique used is multiple linear regression analysis. The results of this study indicate that the work environment and financial compensation have a positive and significant effect on job satisfaction. This means that the better the work environment and the higher the financial compensation given to employees at the Dekuta Hotel, the higher the job satisfaction will be. While role stress variables have a negative and significant effect on job satisfaction. This means that the lower the role stress experienced by Dekuta Hotel employees, the more it will increase employee job satisfaction. Keywords: work environment, role stress, financial compensation, job satisfaction Keywords: work environment, role stress, financial compensation, job satisfaction